She must have been sleeping around” Contextual interpretations of cervical cancer and views regarding HPV vaccination for adolescents in selected communities in Ibadan, Nigeria (2018)
Background Human Papilloma virus (HPV) vaccines for adolescents are pivotal in the control of cervical cancer, the commonest women specific malignancy in sub-Saharan Africa. Knowledge about cervical cancer have been reported to be low in Africa but expressed acceptability for HPV vaccines have been high. The reason for this mismatch is not clear. An understanding of the interpretation of cervical cancer and views about HPV vaccine are important as they can affect actual decision making regarding adolescents' uptake of HPV vaccine. This study explored contextual interpretations of stakeholders regarding cervical cancer and HPV vaccines for adolescents in five selected communities in Ibadan, Nigeria. Methods Qualitative data were collected through twenty focus group discussions among parents of adolescents, religious and traditional leaders, school teachers and adolescents; and four key informant interviews with the identified traditional healers in the selected communities. Constant comparison analysis was done after transcription. Results Almost every group had at least one person who had seen a cervical cancer patient. Cervical cancer was widely viewed as being caused by promiscuity of women while older participants believed that the alteration of lifestyle by civilization was a major contributory factor. There was also a general notion that it was due to a curse. The role of HPV was generally not known. Most participants were favorable towards HPV immunization for adolescents, but traditional healers and some religious leaders were not. The high cost of the vaccines and possibility of side effects where the main concerns about the introduction of HPV vaccine. Decision to take the vaccine rest with the fathers whose views were heavily influenced by traditional and religious leaders. Conclusions Awareness about cervical cancer may not be as low as earlier reported and there were many misconceptions about cervical cancer in the study communities. It is important to address these misconceptions to ensure successful introduction of HPV vaccine for adolescents in future.